Production Of Social Consent in Digital Communication: An Analysis of Togg's Shares on The X Platform (Third Sector Social Economic Review, 2025)
In today's world, where the impact of digital communication in the public sphere is increasing, the X platform has become an important tool for institutions in their efforts to influence and guide public opinion. The aim of this study is to reveal how social consent is produced in digital communication environments. In this context, the posts of TOGG, Turkey's domestic automobile brand, on the X platform between December 23, 2019, and May 1, 2025, were analyzed using content analysis and semiotic analysis techniques. The research was conducted within the framework of Lippmann's public opinion theory, Bernays' consent engineering approach, and Chomsky-Herman's propaganda model. The analysis revealed that TOGG aims to produce social consent at both the emotional and ideological levels through themes such as domestic and national emphasis, cultural symbols, production successes, and accessibility.
Keywords: Social Consent Production; Consent Engineering; Digital Communication; Public Relations; TOGG